Evaluation of the red mud and quartz sand on reinforced metazeolite-based geopolymer composites - Aygormez, Yurdakul (ELSEVIER, 2021)
In the production of geopolymer, which is an environmentally friendly material, it is important to use products with different binding material potential. Zeolite, which is a natural and common, and low-cost material, and red mud (RM), which is a by-product in the alumina refining industry, were used as binding materials. Calcined zeolite (metazaeolite (MZ)) was replaced with red mud in four different proportions (25%, 50%, 75%, and 100% by wt.). Besides, standard sand was replaced with quartz sand (QS) as a different aggregate in five different proportions (20%, 40%, 60%, 80%, and 100% by wt.). The mechanical properties (compressive strength, flexural strength, ultrasonic pulse velocity (UPV)) of the prepared 10 series were investigated in three different days (7, 28, and 56). In addition, the samples were subjected to the high-temperature test (250, 500, and 750 degrees C) and the freeze-thaw test of 400 cycles after 56 days. After the durability tests were completed, the strength, UPV, and weight loss were determined. In addition, SEM analyzes were performed before and after the high-temperature and freeze-thaw tests. According to the results, it was seen that the use of red mud at a rate of 25% contributed to geopolymerization (a 12% increase in compressive strength) and showed this at the end of the durability tests. By using quartz sand up to 40%, increasing the SiO2 ratio increased the results (a 30% increase in compressive strength). Nevertheless, it was seen that stability for all samples was preserved after the durability tests.
Keywords: Geopolymer; Metazeolite; Red mud; Quartz sand; High-temperature test; Freezing-thawing test; FLY-ASH; NATURAL ZEOLITE; METAKAOLIN; CONCRETE; STRENGTH; BEHAVIOR; PERFORMANCE; DURABILITY; CEMENT; WASTE; Construction & Building Technology; Engineering